Strategi Pemasaran Produk Vco (Virgin coconut Oil) di Rumah Produksi Kena Ketik Nita - Felisitas Lusclarita (Jurnal Ilmiah Wahana Pendidikan, 2022)
VCO (Virgin Coconut Oil) is a pure coconut oil made from fresh coconut meat that is processed in low temperatures or without heating. The important content in the oil can still be maintained, and the oil has a clearer color and can last for two years without rancid. Pure coconut oil (VCO) is a high-grade coconut oil that has a low water content and free fatty acid content, clear in color, smells good, its shelf life is more than 12 months, does not contain cholesterol, and lauric acid is converted into monolaurin so that it is anti-viral. This research aims to find out the marketing strategy of VCO (Virgin Coconut Oil) products at the Nita Type Kena Production House. This type of study used 15 interview samples taken, including employees and general buyers. The results of the interview are processed using purposive sampling methods and SWOT analysis. The results of this study show that: VCO (Virgin Coconut Oil) Product Marketing Strategy at Kena Tipe Nita Production House, namely, increasing the price of VCO products by paying attention to production facilities and strategic business locations, increasing profits by increasing pure coconut oil production through regular labor utilization and working time